2021
DOI: 10.1001/jamapediatrics.2021.2041
|View full text |Cite
|
Sign up to set email alerts
|

Association of High Screen-Time Use With School-age Cognitive, Executive Function, and Behavior Outcomes in Extremely Preterm Children

Abstract: IMPORTANCEBoth preterm birth and increased screen time are known to be associated with an increase in risk of developmental and behavioral sequelae. The association between high screen time or a television or computer in the bedroom in early school age and adverse cognitive, executive function, language, and behavior outcomes of extremely preterm children (EPT) is not well understood.OBJECTIVE To assess the association of high screen time with cognition, language, executive function, and behavior of EPT childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…In contrast, only 31% of schoolchildren below 13 years in China had higher screen time before the COVID-19 pandemic 23. In another study done before the pandemic, 57% of extremely preterm children and 55.3% of healthy preschool children had high screen time, and 266 (64%) had a television/computer in their bedroom 24 25. Among the schoolchildren aged 3–13 years in China, 77% engaged in prolonged screen time 26.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, only 31% of schoolchildren below 13 years in China had higher screen time before the COVID-19 pandemic 23. In another study done before the pandemic, 57% of extremely preterm children and 55.3% of healthy preschool children had high screen time, and 266 (64%) had a television/computer in their bedroom 24 25. Among the schoolchildren aged 3–13 years in China, 77% engaged in prolonged screen time 26.…”
Section: Discussionmentioning
confidence: 98%
“… 23 In another study done before the pandemic, 57% of extremely preterm children and 55.3% of healthy preschool children had high screen time, and 266 (64%) had a television/computer in their bedroom. 24 25 Among the schoolchildren aged 3–13 years in China, 77% engaged in prolonged screen time. 26 Neighbouring India has few studies on screen time; 84%–89.4% of children aged 2–5 years had screen time of more than 1 hour a day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, ADHD and its co-occurrent behaviors have been found to be associated with increased screen time utilization (STU). 11 , 12 , 13 , 14 , 15 , 16 , 17 STU refers to the time spent with any screens, including smartphones, tablets, television, or computers. With a growing number of children's leisure time spent on screens in recent years, 18 concerns have been raised that excessive STU would result in psychological and cognition problems in children.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that boys and children born preterm tend to spent more time on digital media. 4,19 Consistent with the previous findings, we found that boys spent more time playing video games compared to girls (boys = 1.25 [1.15]; girls = 0.63 [0.84]; P unadj <.001), this was also the case for children born preterm (preterm = 1.02 [1.09]; full-term = 0.94 [1.05]; P unadj =.02). We also did a separate regression analysis (Model 1 and 2) for subgroups and found a negative association between playing video games and global cortical surface area in boys (β = -0.04 [-0.07 -0.005]; P=.02) and in children born at term (β = -0.03 [-0.05 -0.007]; P unadj =.01) but not girls (β = -0.02 [-0.06 -0.007]; In an additional attempt to correct for the smaller brain at baseline, we built a model (Models 4 and 5), accounting for the baseline brain measure as an additional covariate to the pre-existing covariates for the longitudinal analyses (as described in the methods).…”
Section: Primary Outcomementioning
confidence: 99%